Environmental attitudes and behaviour of birdwatchers: a missing link Environmental attitudes and behaviour of birdwatchers: a missing link - Guimarães, Maria (2022)
Birdwatching is one of the fastest growing sectors of ecotourism. Managing this nature-based activity requires understanding birdwatchers’ attitudes and behaviour towards the natural environment. This paper proposes assessing these attitudes and the link to behavioural intentions by combining the New Environmental Paradigm (NEP) with a criterion-based segmentation method, the chi-squared automatic interaction detector (CHAID). This methodology was applied through a survey questionnaire to birdwatchers in the Ria Formosa Natural Park, a wetland located in South Portugal. The amount birdwatchers were willing to pay for an improvement in the environmental quality of the site, a behavioural intention variable, was used as the criterion in the CHAID analysis. Two birdwatcher segments willing to pay above average were identified and labelled as ‘environmental stewards’ and ‘birdwatching fans’. A key result that emerged from our study is that the NEP score is not a significant predictor of the willingness to pay for environmental improvement in the CHAID analysis. Hence, there is a missing link, as pro-environmental attitudes do not translate into pro-environmental behavioural intentions.